Dipturus batis Linnaeus 1758 ... - Gordon, Cat A.; Hood, Ali R.; Ellis, Jim R. (Zenodo, 2016)
Dipturus batis (Linnaeus, 1758) Distribution. Blue (or grey) skate (D. batis, the form described by Iglésias et al. (2010) as Dipturus cf. flossada) generally has a more southerly distribution than Dipturus cf. intermedia (Parnell, 1837) however the distribution of both species overlaps in the area from the Celtic Sea to northwest Scotland (Griffiths et al., 2010). Material examined. Twenty-four eggcases were examined for this study. Most samples (n = 22) were removed from mature females that were captured by gillnet on the fishing grounds west of the Isles of Scilly (Bendall et al., 2012). The remaining two eggcases examined were museum specimens collected from Scarborough (BMNH 1928.11.1.1–2). Two D. batis eggcases found on Perranporth Beach (northern Cornwall) in July 2014 were reported to the Great Eggcase Hunt in March 2015 (and identification confirmed from photographs), however they were not available for measurement. Description. The eggcase of D. batis (Figure 4 a) is a similar shape to that of D. ... : Published as part of Gordon, Cat A., Hood, Ali R. & Ellis, Jim R., 2016, Descriptions and revised key to the eggcases of the skates (Rajiformes: Rajidae) and catsharks (Carcharhiniformes: Scyliorhinidae) of the British Isles, pp. 255-280 in Zootaxa 4150 (3) on page 260, DOI: 10.11646/zootaxa.4150.3.2, http://zenodo.org/record/272101 ...